2012
DOI: 10.3892/ijmm.2012.1142
|View full text |Cite
|
Sign up to set email alerts
|

GPR40: A therapeutic target for mediating insulin secretion

Abstract: G-protein-coupled receptor 40 (GPR40), known as free fatty acid receptor 1, is mainly expressed in pancreatic β-cells and activated by medium- and long-chain fatty acids. Increasing evidence indicates that the activation of GPR40 in cells causes insulin secretion, and GPR40 has become an attractive therapeutic target for type 2 diabetes. Recently, certain novel GPR40 agonists have been identified that regulate glucose-stimulated insulin secretion, leading to the development of new drugs for the treatment of ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 91 publications
(90 reference statements)
0
32
0
Order By: Relevance
“…GPR40, a G protein-coupled receptor also called FFA1, is expressed abundantly in the pancreatic β-cells and serves as receptor for long-chain FFAs 30 . It has been shown that activation of GPR40 by long-chain FFAs leads to an enhanced β-cell response to glucose in the secretion of insulin 31 .…”
Section: Discussionmentioning
confidence: 99%
“…GPR40, a G protein-coupled receptor also called FFA1, is expressed abundantly in the pancreatic β-cells and serves as receptor for long-chain FFAs 30 . It has been shown that activation of GPR40 by long-chain FFAs leads to an enhanced β-cell response to glucose in the secretion of insulin 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, free fatty acids have also been reported to stimulate insulin secretion in a glucose-dependent manner by activation of GPR40 (free fatty acid receptor 1 or FFAR1) [154156]. Thus, several GPR40 agonists are being developed such as TAK-875, which was shown both in rodents and humans to enhance insulin secretion and promote glucose control [155, 157].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…In fact a number of small molecule agonists have been shown to modulate glucose stimulated insulin secretion. Different GPR40 agonists such as GW9508, TAK-875, AS2575959, AMG837 and phenyl propanoic acid derivatives have shown increased insulin secretion in both insulinoma cells and/or in animal models [16-20]. Among these agonists, TAK-875 has been shown to prevent β-cells dysfunction [21] in animal model of diabetes and improves glycemic control in T2DM patients [22,23].…”
Section: Introductionmentioning
confidence: 99%